PEMANFAATAN SISTEM INFORMASI MUTASI KENDARAAN SAMSAT KOTA JAMBI: Application, Vehicle Mutation Data, Web, MySQL Database - -, Nilawati (JURNAL AKADEMIKA, 2019)
Samsat Jambi is a tax office and business. In carrying out activities such as vehicle mutations. Vehicle mutation is an attempt to take care of administration regarding the transfer of vehicle identification from the area of ​​origin to the destination area which is adjusted by moving from the new vehicle owner's address. The process of processing vehicle mutation data is still manually, which in its manufacture still uses the Microsoft Excel application which has to do editing each time it will do the administration of vehicle mutations. In Microsoft Excel, there are now many deficiencies that must be faced every time typing errors occur in inputting data are done repeatedly, and also searching for the desired mutation data so that it takes longer. This causes the functions related to Samsat Jambi operational activities can not be carried out optimally. In this thesis report, a vehicle mutation information system is made that is used to assist or facilitate the processing of Samsat Jambi in managing vehicle mutation data in the form of taxpayer data input, and a vehicle physical check report. The development of the software uses the WEB programming language, PHP using the Mysql database. From this study produced a vehicle mutation information system design that can facilitate the processing of Jambi Samsat in data processing vehicle mutations and report generation.